Fayzulla LINGUA CULTURAL FEATURES OF NEOLOGISM: LINGUA CULTURAL FEATURES OF NEOLOGISM - Usanov, Fayzulla (Журнал иностранных языков и лингвистики, 2022)
Neologisms are lexical units that are new not only in form or content at some fixed point in time, but also having new sociocultural reference and functioning in demand conceptual spheres given by the society. Rational integrated methodology for identifying the national-cultural component of the denotative and connotative meanings of neologism is a combination of diachronic, contrastive, definitional and conceptual analysis. Sociocultural specifics of neonomination in concrete history